Evaluation of the antibacterial activity of cultivated Caucasian whortleberry (Vaccinium arctostaphylos L.) against fish pathogens - Terzi, Ertugrul; Tahiluddin, Albaris B.; Kadak, Ali Eslem (Walter de Gruyter GmbH, 2023)
Abstract Bacterial diseases are one of the major factors hampering aquaculture sustainability. Antibiotics are used widely to treat or prevent infectious bacterial diseases in aquaculture. However, because of growing problems of antibiotic resistance caused by the imprudent use of antibiotics, sourcing environmentally benign alternatives, such as herbal/medicinal plants, is now the focus of many researchers. Hence, in this study, a minimum inhibitory concentration (MIC) test with broth microdilution was performed to determine the in vitro antibacterial activity of an aqueous methanolic extract of cultivated Caucasian whortleberry (Vaccinium arctostaphylos L.) against various fish pathogens, i.e., Yersinia ruckeri, Pseudomonas putida, P. luteola, Aeromonas salmonicida, A. hydrophila, and A. sobria. The results revealed that the MIC values of the aqueous methanolic extract against Y. ruckeri, P. putida, P. luteola, A. salmonicida, and A. hydrophila were 8.75 mg mL−1, while against A. sobria it was 2.19 mg mL−1. This study indicated that the medicinal plant V. arctostaphylos L. can potentially be used against all the fish pathogens tested thanks to its various important bioactive compounds. However, to assess the potential of this plant, further in vivo studies should be carried out.
Keywords: bioactive compounds; bacterial diseases; medicinal plant; fish health management; Aquaculture. Fisheries. Angling; SH1-691; minimum inhibitory concentration; 2. Zero hunger; 14. Life underwater; 15. Life on land; 6. Clean water; 3. Good health